The Effect of Ginger Compress Therapy and Kinesiotaping on Pain and Stiffness in the Joints and Functional Ability in Elderly with Osteoarthritis - Achmad Syukkur; Maria Astrid; Sutanto Priyo Hastono (Babali Nursing Research, 2020)
Introduction: Osteoarthritis is a slowly progressive non-inflamation in diarthrodial (synovial) joints which increasingly occurs as one ages, showing such initial symptom as pain in the joints during activities. The pain gets worse over time, causing the obstruction of joint movements and affects the patient’s functional ability. The aim of the study was to identify the effect of red ginger compress therapy and kinesio tapping on pain and stiffness in the joints and functional ability. Methods: This research used the Quasi Experiment pre and post test design with control group. A simple random technique to collect 112 respondents who were devided into intervention group receiving red ginger compress therapy, kinesiotaping group, combination of red ginger compress therapy and kinesiotaping group, and control group, each of which consisted of 28 respondents in Pangesti Elderly Home Lawang and Pangesti Tresno Mukti Elderly Home Turen. Results: Evaluation based on WOMAC index was applied on day one, three, five and seven. The result of ANCOVA showed the red ginger compress intervention with p = 0.005, kinesiotaping with p = 0.005 and red ginger compress + kinesiotaping with p = 0.005 in reducing pain, joint stiffness and difficulty functional ability. Conclusion: This research findings are expected to be one of non-pharmcological therapies recommended to patients with OA.